The Influence of Financial Report Preparation Skills, Financial Literacy, and Accounting Information Systems on the Performance of MSMEs in Cirebon Regency - Mia Febriyanti; Itat Tatmimah; Muzayyanah (Universitas Sains dan Teknologi Komputer, 2025)
This study investigated the influence of financial report preparation skills, financial literacy, and accounting information systems on the performance of micro, small, and medium enterprises (MSMEs) in Cirebon Regency. The research adopted a quantitative approach with a causal associative design. Data were collected through closed-ended questionnaires distributed to 100 culinary-sector MSMEs selected using purposive sampling. The data analysis involved validity and reliability testing, classical assumption tests, and multiple linear regression. The findings revealed that financial report preparation skills, financial literacy, and accounting information systems had both partial and simultaneous positive effects on MSME performance. Specifically, the ability to prepare financial statements and the use of accounting systems significantly enhanced operational efficiency and financial outcomes, while financial literacy contributed to better financial decision-making. The study concluded that improving financial competencies and adopting technology-based accounting practices are key drivers for strengthening MSME performance in the region